(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Migrant workers face significant challenges in maintaining continuous and accessible healthcare records due to frequent relocation, limited infrastructure, and reliance on paper-based systems. These issues often lead to loss of medical history, repeated diagnostic procedures, increased healthcare costs, and delays in treatment. Existing digital healthcare solutions, including cloud-based and blockchain-based systems, are often unsuitable for low-resource environments due to their dependence on continuous internet connectivity, high implementation cost, and complex infrastructure requirements. This paper proposes a Digital Health Record Management System based on a client-first architecture that enables offline data storage and retrieval directly on the user’s device. The system integrates QR-based identification for instant access to patient records, multilingual support for improved usability, and lightweight data management techniques suitable for low-resource settings. Unlike traditional systems, the proposed approach eliminates dependency on centralized servers and provides a portable and cost-effective solution tailored for migrant populations. Experimental evaluation using a simulated dataset demonstrates that the system reduces data retrieval time from approximately 15–20 seconds to 2–3 seconds, achieving an improvement of nearly 70–80%. Additionally, the system ensures 100% offline accessibility and minimizes the risk of data loss associated with physical records. Usability testing indicates improved efficiency, faster navigation, and ease of use for non-technical users. The proposed system highlights the potential of client-side digital healthcare solutions in improving accessibility, efficiency, and continuity of care in underserved environments. It also provides a scalable foundation for future enhancements, including cloud integration, advanced security mechanisms, and healthcare interoperability standards.